2022
DOI: 10.1097/rli.0000000000000850
|View full text |Cite
|
Sign up to set email alerts
|

Basic and Advanced Metal-Artifact Reduction Techniques at Ultra-High Field 7-T Magnetic Resonance Imaging—Phantom Study Investigating Feasibility and Efficacy

Abstract: Objectives: The aim of this study was to demonstrate the feasibility and efficacy of basic (increased receive bandwidth) and advanced (view-angle tilting [VAT] and slice-encoding for metal artifact correction [SEMAC]) techniques for metalartifact reduction in ultra-high field 7-T magnetic resonance imaging (MRI). Materials and Methods: In this experimental study, we performed 7-T MRI of titanium alloy phantom models composed of a spinal pedicle screw (phantom 1) and an intervertebral cage (phantom 2) centere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…22,23 Recent advances in metal-artifact reduction at ultra-high-field strength have also made it possible to reduce peri-implant signal voids and geometric distortions in the presence of metal with a combination of increased receive bandwidth, view-angle tilting, as well as slice-encoding for metal artifact correction. 24 The extent of metal artifacts is directly proportional to the field strength. 25 Therefore, metal artifact techniques at 7 T MRI will help obtain a homogeneous signal intensity in patients undergoing 7 T MRI, for example, after ACL or tendon reconstructions.…”
Section: Clinical Use Cases For 7 T Mrimentioning
confidence: 99%
“…22,23 Recent advances in metal-artifact reduction at ultra-high-field strength have also made it possible to reduce peri-implant signal voids and geometric distortions in the presence of metal with a combination of increased receive bandwidth, view-angle tilting, as well as slice-encoding for metal artifact correction. 24 The extent of metal artifacts is directly proportional to the field strength. 25 Therefore, metal artifact techniques at 7 T MRI will help obtain a homogeneous signal intensity in patients undergoing 7 T MRI, for example, after ACL or tendon reconstructions.…”
Section: Clinical Use Cases For 7 T Mrimentioning
confidence: 99%
“…However, the limitations of DTI have been demonstrated in providing post-surgery information 4 . High-intensity geometric distortions arise due to the presence of metal in the imaging plane or in the adjacent plane, also known respectively as in-plane and through-plane artifacts 13,21 . It has been shown that the size and the intensity of metal-induced artifacts increase with magnetic eld strength and employed pulse sequence parameters such as the echo spacing and the receiver bandwidth 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Even with these new improvements, postsurgical metallic implants typically induce dramatic magnetic eld inhomogeneities, leading to severe image distortions. The metal-induced artifact depends on the implant hardware (material, size, shape), the magnetic eld B0 strength, and MRI sequence 13 . Moreover, DTI is often performed using the single-shot Echo Planar Imaging pulse sequence (SS-EPI) due to its fast acquisition speed.…”
Section: Introductionmentioning
confidence: 99%
“…Living tissues can also diminish the image quality due to susceptibility discrepancies, such as those between soft tissues and air holes in the brain. Moreover, embedded matters within the body such as prostheses and particularly metallic ones can also weaken image quality [34][35][36][37][38][39][40]. The image modification due to metallic materials, which present susceptibility variations, depends on the size, the shape and the direction with respect to B 1 [27,29,33].…”
Section: Image Artifactsmentioning
confidence: 99%